2017
DOI: 10.1016/j.nicl.2017.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI to distinguish early onset Alzheimer's disease and behavioural variant of frontotemporal dementia

Abstract: This prospective study explored whether an approach combining structural [cortical thickness and white matter (WM) microstructure] and resting state functional MRI can aid differentiation between 62 early onset Alzheimer's disease (EOAD) and 27 behavioural variant of frontotemporal dementia (bvFTD) patients. Random forest and receiver operator characteristic curve analyses assessed the ability of MRI in classifying the two clinical syndromes. All patients showed a distributed pattern of brain alterations relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 87 publications
(131 reference statements)
5
46
1
1
Order By: Relevance
“…Furthermore, in line with previous work, we observed that concatenating all measures did not result in the most accurate classification model and as more measures were added the level of improvement became less apparent [29,31,61]. The marginal improvements observed for some measures or combinations may indicate a negligible contribution to the model.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, in line with previous work, we observed that concatenating all measures did not result in the most accurate classification model and as more measures were added the level of improvement became less apparent [29,31,61]. The marginal improvements observed for some measures or combinations may indicate a negligible contribution to the model.…”
Section: Discussionsupporting
confidence: 91%
“…Classification methods that combined these measures invariably showed improvement of classification accuracy over models that used these measures separately [15,18,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging imaging techniques, like Multiparametric MRI, are attempting to outline structural differences and resting state differences between the two diagnoses. 6 Some risk factors for dementia, including lower cardiovascular fitness in early life, lower cognitive reserve in early adulthood, and traumatic brain injury (TBI), seem to have a greater impact on these patients. Counterintuitively, these patients have fewer medical comorbidities such as diabetes and other conditions which impact vasculature.…”
Section: Early Onset Alzheimer's Dementia (Eoad)mentioning
confidence: 99%